DAKWAH DAN PENGEMBANGAN MASYARAKAT - Masmuddin Masmuddin (IAIN Palopo, 2010)
In Islam, da’wah and community are inseparable because of being subjected to dakwah in Islam is a community or congregation. In the social life of society is not static, is always changing and evolving in according to the changes and the times. Islam is a doctrine that includes instructions on all aspects of human life, including how that society should change and development. Da'wah in this case provides clues about how people make a change that is positive, including in relation to social life. Because it preaches to contain clues about the changes and development of society.DAKWAH DAN PENGEMBANGAN MASYARAKAT